HUBUNGAN KADAR MDA SPERMA DENGAN INTEGRITAS MEMBRAN SPERMATOZOA TIKUS (Rattus norvegicus) SETELAH PEMAPARAN 2–METHOXYETHANOL - Alfiah Hayati; Soesanto Mangkoewidjojo; Aucky Hinting; Sukarti Moeljopawiro (The East Java Biological Society, 2006)
In the body, 2-methoxyethanol compound may be converted to MAA. MAA is a strong oxidant and may cause oxidation stress in spermatozoa. Oxidation stress is a disturbance on phosphorilation that increases ROS concentration, and it produces lipid peroxide in spermatozoa membrane resulted in high MDA concentration. One of indicator of spermatozoa membrane disturbances is a lack of spermatozoa membrane integrity. The main purpose of this research was to determine the relationship between MDA concentration in sperm and membrane integrity of spermatozoa in rats. The animal of treated groups (n = 40) were divide into 8 groups of 5 each. The rats were given subcutaneous injection with 0,2 ml of 200 mg/kg/day for 1 day (P1), 3 days (P2), 6 days/week (P3), and 12 days/two weeks (P4), respectively the control group was injected with physiological saline of the same volume. The concentration of MDA was measured by spectrophotometer and observing membrane integrity used HOS method to watch the spermatozoa response on hypoosmotic condition. The results of the research indicated that 2-ME caused the increasing in sperm MDA concentration and the decrease of spermatozoa membrane integrity. There was negative correlations between MDA concentration and spermatozoa membrane integrity.